2022
DOI: 10.1007/s40618-021-01704-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term high-dose l-arginine supplementation in patients with vasculogenic erectile dysfunction: a multicentre, double-blind, randomized, placebo-controlled clinical trial

Abstract: Purpose The current randomized, double-blind, placebo-controlled clinical trial addressed the effects on penile erectile function of relatively high daily oral doses (6 g/day) of l-ARG for 3 months (N = 51) compared to placebo (N = 47), in patients with vasculogenic ED, with comparison between mild–moderate and severe vasculogenic ED. Methods The outcome measures included IIEF-6 score and cavernous arteries peak systolic flow velocity (PSV) at dynamic peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Some evidence suggests that empiric therapies may have a role in diabetic patients non-responding to PDE5i without causing any serious adverse effects. [67][68][69][70] For example, L-arginine is a NO precursor which is therefore necessary for smooth muscle relaxation in the cavernous corpora. 71 Likewise, nicotinic acid is related to energy production in the endothelium and is a vasodilator and thus may improve erectile function.…”
Section: Antioxidant Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that empiric therapies may have a role in diabetic patients non-responding to PDE5i without causing any serious adverse effects. [67][68][69][70] For example, L-arginine is a NO precursor which is therefore necessary for smooth muscle relaxation in the cavernous corpora. 71 Likewise, nicotinic acid is related to energy production in the endothelium and is a vasodilator and thus may improve erectile function.…”
Section: Antioxidant Supplementationmentioning
confidence: 99%
“…Some evidence suggests that empiric therapies may have a role in diabetic patients non‐responding to PDE5i without causing any serious adverse effects 67–70 . For example, l ‐arginine is a NO precursor which is therefore necessary for smooth muscle relaxation in the cavernous corpora 71 .…”
Section: Treatment Modalities To Treat Erectile Dysfunctionmentioning
confidence: 99%
“…The study compared the outcomes of mild- moderate and severe vasculogenic erectile dysfunction. The results of the study showed no serious complications reported in patients who received L-arginine [ 46 ]. In our study, the patients reported no dangerous side effects or injuries.…”
Section: Discussionmentioning
confidence: 99%